Rancang Bangun dan Studi Eksperimental Pengaruh Perbedaan Jarak Pitch dan Kemiringan Poros terhadap Kinerja Mekanik Model Turbin Ulir 2 Blade Pada Aliran Head Rendah - Yul Hizhar; Bambang Yulistianto; Suryo Darmo (Department of Mechanical Engineering, Universitas Andalas, 2017)
Screw turbine uses low head and high flow rate of water to generate rotation speed. Screw turbine has many advantages such as simple in construction and installation, low cost in operating and maintenance, and fish-friendly. The influencing parameters to mechanics performance of screw turbine are pitch distance and the shaft slope. The purposes of this research are to design 2-blades screw turbine model and to test the influence of pitch distance variation and shaft slope to mechanics performance in laboratory. This research used experimental method which each of screw turbine model with pitch of 2Ro, 1.6Ro, and 1.2Ro were tested in variation of shaft slope of 25˚, 30˚, 35˚, 40˚, and 45˚. The water flow rate was 0.00728 m3/s. The data was acquisitioned at Hydraulics Laboratory Civil Diploma Universitas Gadjah Mada. The result of testing without load showed that screw turbine model pitch of 2Ro had the higher rotation speed than pitch of 1.6Ro and 1.2Ro which the highest rotation speed was 255 rpm at shaft slope of 35˚. The result of testing with load showed that each turbine produced the highest rotation speed and output power at the shaft slope of 35°, meanwhile the highest efficiency was produced at the shaft slope of 25°. The result of research showed that generally screw turbine model pitch of 2Ro produced the higher mechanics performance (output power and efficiency) than pitch of 1.6Ro and 1.2Ro. At the shaft slope of 25°, pitch 2Ro produced power 15.89 W and efficiency 73.08% (the highest), meanwhile at the shaft slope of 35°, pitch 2Ro produced power 18.51 W (the highest) and efficiency 66.16%. These efficiencies result difference were caused by the influence of the difference of hydropower (input power) at the variations of the shaft slopes.